A green synthesis of bis[1-(hydroxy-κO)-2(1H)-pyridinethionato-κS2]-(T-4)-zinc (zinc pyrithione) nanoparticles via mechanochemical milling. Issue 2 (22nd January 2016) - Kalantar, Thomas H.; Foley, Paul; Tucker, Christopher J.; Felix, Mark S.; Rozeveld, Steven J.; Harris, Joseph D.; Crowder, Cyrus E.; Howard, Kevin E.
Abstract : Particulate bis[1-(hydroxy- κO )-2(1 H )-pyridinethionato- κS 2 ]-( T -4)-zinc (zinc pyrithione; ZPT) in the diameter range 0.5–0.7 µm is a US FDA-approved anti-dandruff active widely used in anti-dandruff shampoos. A nanoparticulate form of ZPT is expected to exhibit a higher activity, be distributed more effectively on the scalp, require less thickening agent in the shampoo formulation to ensure its stability against settling than the standard form of ZPT, and would enable clear anti-dandruff shampoo formulations. We demonstrate, for the first time, that a green, mechanochemical nanoparticle synthesis process can be used to prepare nanoparticulate ZPT from zinc chloride and sodium pyrithione monohydrate. Both a Reeves attrition mill and a Retsch MixerMill were found to be effective tools for delivering the mechanical energy needed for the conversion. The infrared spectra and X-ray powder diffraction patterns for the products correspond to those for the known desired material. Transmission electron microscopic analysis indicates that ZPT nanoparticles with primary particle diameters in the range of 20–200 nm (mean diameters of 65–100 nm) can be obtained via this method.